Where the red fern grows ebook - Rawls, Wilson (2011)
A beloved classic that captures the powerful bond between man and man’s best friend.   Billy has long dreamt of owning not one, but two, dogs. So when he’s finally able to save up enough money for two pups to call his own—Old Dan and Little Ann—he’s ecstatic. It doesn’t matter that times are tough; together they’ll roam the hills of the Ozarks. Soon Billy and his hounds become the finest hunting team in the valley. Stories of their great achievements spread throughout the region, and the combination of Old Dan’s brawn, Little Ann’s brains, and Billy’s sheer will seems unbeatable. But tragedy awaits these determined hunters—now friends—and Billy learns that hope can grow out of despair, and that the seeds of the future can come from the scars of the past.   Praise for Where the Red Fern Grows   A Top 100 Children’s Novel, School Library Journal ' s  A Fuse #8 Production A Must-Read for Kids 9 to 14, NPR Winner of Multiple State Awards Over 7 million copies in print!   “Very touching.” — The New York Times Book Review   “One of the great classics of children’s literature . . . Any child who doesn’t get to read this beloved and powerfully emotional book has missed out on an important piece of childhood for the last 40-plus years.” — Common Sense Media   “An exciting tale of love and adventure you’ll never forget.” — School Library Journal   “A book of unadorned naturalness.” — Kirkus Reviews   “Written with so much feeling and sentiment that adults as well as children are drawn [in] with a passion.” — Arizona Daily Star   “It’s a story about a young boy and his two hunting dogs and . . . I can’t even go on without getting a little misty.” — The Huffington Post    “We tear up just thinking about it.” — Time on the film adaptation